2008
DOI: 10.1063/1.2990755
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the antiparallel magnetic alignment of adjacent Fe and MnAs thin films

Abstract: The magnetic coupling between iron and α-MnAs in the epitaxial system Fe/MnAs/GaAs(001) has been studied at the sub-micron scale, using element selective x-ray photoemission electron microscopy. At room temperature, MnAs layers display ridges and grooves, alternating α (magnetic) and β (non-magnetic) phases. The self-organised microstructure of MnAs and the stray fields that it generates govern the local alignment between the Fe and α-MnAs magnetization directions, which is mostly antiparallel with a marked de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…It is worthwhile to notice that both MFM images indicate that the magnetization depth profile ͑along the ͓1100͔ MnAs axis͒ at the edges of the sample is uniform, i.e., magnetic domains look like bar magnets whose magnetization directions are aligned along the easy axis ͑type I magnetic domains͒. 16 In two previous works, it was shown that this ␣ − ␤ modulation creates dipolar magnetic fields so intense that they can reverse the magnetization of a overlying Fe thin film 17,18 and pin the wall strongly to the interstripe region. 19 Here again, we find evidences of an intense stray field far inside the GaAs substrate ͑more then 200 nm from the MnAs/GaAs interface͒.…”
mentioning
confidence: 97%
“…It is worthwhile to notice that both MFM images indicate that the magnetization depth profile ͑along the ͓1100͔ MnAs axis͒ at the edges of the sample is uniform, i.e., magnetic domains look like bar magnets whose magnetization directions are aligned along the easy axis ͑type I magnetic domains͒. 16 In two previous works, it was shown that this ␣ − ␤ modulation creates dipolar magnetic fields so intense that they can reverse the magnetization of a overlying Fe thin film 17,18 and pin the wall strongly to the interstripe region. 19 Here again, we find evidences of an intense stray field far inside the GaAs substrate ͑more then 200 nm from the MnAs/GaAs interface͒.…”
mentioning
confidence: 97%
“…[12][13][14] Beside its peculiar magnetic properties, Fe/MnAs/GaAs͑001͒ is also interesting from a purely structural perspective. [12][13][14] Beside its peculiar magnetic properties, Fe/MnAs/GaAs͑001͒ is also interesting from a purely structural perspective.…”
mentioning
confidence: 99%
“…1͑a͔͒. In previous studies, [6][7][8] we found that the ␣-␤ modulation creates dipolar magnetic fields ͑H D ͒ extending above the MnAs template.…”
mentioning
confidence: 81%